2014
DOI: 10.4028/www.scientific.net/amr.996.729
|View full text |Cite
|
Sign up to set email alerts
|

Stress Relaxation in Shot-Peened Geometric Features Subjected to Fatigue: Experiments and Modelling

Abstract: This paper investigates experimentally and numerically the degree to which the stress relaxation in shot-peened simple geometric features of steel turbine materials can be modelled by using an understanding of simple eigenstrain distributions. The residual stress is determined as the elastic response of whole component when the plastic strains caused by shot peening is incorporated as an eigenstrain in an appropriate finite element (FE) model. The application of a subsequent live load is then modelled as an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Based on previous findings , N = 8 has been chosen for the T0 process and the corresponding depth of the eigenstrain distribution has been assumed to be 0.4 mm. Using the same approach, N = 4 and a eigenstrain depth of 0.2 mm were determined for the T1 process.…”
Section: Numerical Modelling and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous findings , N = 8 has been chosen for the T0 process and the corresponding depth of the eigenstrain distribution has been assumed to be 0.4 mm. Using the same approach, N = 4 and a eigenstrain depth of 0.2 mm were determined for the T1 process.…”
Section: Numerical Modelling and Discussionmentioning
confidence: 99%
“…The authors have previously presented the logic of an eigenstrains‐based FE modelling of residual stresses and the relaxation of residual stress in a shot‐peened flat geometry. The work presented in the paper is limited to a single geometry and a simple material model (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…12 Additionally, for relatively extreme Low-Cycle Fatigue (LCF) conditions (<10,000 cycles), the application of relatively high strain ranges (>1%) can relax the compressive residual stress produced from shot peening within the first 1% of fatigue life for FV448 material. 5,9,[13][14][15] With a diminished compressive residual stress field, the retardation effect from shot peening on short crack propagation is no longer apparent. Studies have shown that the benefits of shot peening outweigh the drawbacks for the majority of fatigue situations, resulting in an improved resistance to fatigue overall, including for in-service turbine blades in low-cycle fatigue conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for relatively extreme Low‐Cycle Fatigue (LCF) conditions (<10,000 cycles), the application of relatively high strain ranges (>1%) can relax the compressive residual stress produced from shot peening within the first 1% of fatigue life for FV448 material 5,9,13–15 . With a diminished compressive residual stress field, the retardation effect from shot peening on short crack propagation is no longer apparent.…”
Section: Introductionmentioning
confidence: 99%